String Tension in Traditional Kite Games as a Physics E-Supplement Design - Fitrie Rahayu, Afira; Lesmono, Albertus Djoko; Yushardi (Indonesian Journal of Science and Education, 2025)
Physics studies the meaning of how a phenomenon can occur, both natural phenomena, human activities, and other living things. The traditional kite game is one of the human activities that includes the concept of physics, one of which is the tension of string. This study examines how tension in the string occurs in the kite string and the effects of several variables such as differences in the length of the string, the surface area of ​​the kite, and the angle of the puddles on the value of the tension in the string as a descriptive description of the concept of string tension. The method used is a qualitative method with a content analysis approach with stages of unitizing, selecting, recording, reducing, inferring, and narrating. String tension occurs when a lifting force that affects kite also affects the thread so that it is also pulled up and because the thread is extended to a certain length, the tension in the string occurs. The value of string tension will be greater as the length of the thread and the surface area of ​​the kite increase. However, the value of the tension in the rope will decrease with increasing the angle of the swivel used.